Spatial and temporal representativeness of water monitoring efforts in the Baltic Sea coast of SW Finland - Erkkila A.; Kalliola R. (the Geographical Society of Finland, 2022)
Traditional in situ surface water sampling produces accurate information on water chemistry and biology. Such sampling is conducted primarily as part of water quality monitoring programmes. If sufficiently consistent, the once collected water quality data could also provide valuable resources for subsequent use in scientific research and long-term monitoring. We examined the spatial and temporal coherence of the archived data resources stored in the environmental information system of the Finnish Environmental Administration (the Hertta-PIVET register). We used phytoplankton chlorophyll-a and primary productivity data collected during 1971–2006 as sample resources for environmental studies on the highly fragmented SW coast of Finland (Northern Baltic Sea). 733 sampling stations were categorized according to the total number of sampling days, the consistence of sampling, the number of representative years and the continuity of sampling. Considerable spatial and temporal inconsistencies were observed, making the accumulated data resources rather unsuitable for many types of environmental studies. Synchronization of sampling activities could improve the representativeness of spatial and temporal coverage of regional sampling. Strategic planning of sampling is required to achieve more concerted data generation activities and to facilitate long-term spatially representative analyses.